Beyond Viral Load: The Clinical and Endocrine Profile of ART-Naive HIV-Infected Men with Hypogonadism, Opportunistic Infections, and Malnutrition - Yulianto Kusnadi; Fahrenheit; Harun Hudari (HM Publisher, 2025)
In patients with advanced human immunodeficiency virus (HIV), the clinical presentation often extends beyond immunodeficiency to a syndemic of interacting comorbidities. Male hypogonadism is a critical but often under-recognized endocrine dimension of this syndrome. This study aimed to characterize the clinical, metabolic, and endocrine profile of antiretroviral therapy (ART)-naive men to provide a comprehensive baseline understanding of this syndemic state before therapeutic intervention. An analytical cross-sectional study was conducted from April to October 2024, enrolling 64 consecutively presenting ART-naive men with HIV at a tertiary hospital in Palembang, Indonesia. We performed a comprehensive assessment including WHO clinical staging, nutritional evaluation (BMI), and screening for comorbidities. Endocrine status was assessed by measuring total testosterone, Luteinizing Hormone (LH), and serum albumin, from which bioavailable testosterone was calculated using the Vermeulen formula. Bivariate correlations and comparative analyses were conducted to explore relationships between variables. The cohort presented with profound immunodeficiency (median CD4 count: 23.5 cells/µL) and advanced disease (92.2% in WHO Stage 3 or 4). A high burden of opportunistic infections (40.6% pulmonary tuberculosis) and malnutrition (48.4% underweight; median serum albumin: 3.25 g/dL) was observed. Based on total testosterone (<300 ng/dL), the prevalence of hypogonadism was 32.8%. However, analysis using the more physiologically relevant calculated bioavailable testosterone (<70 ng/dL) revealed a higher prevalence of 42.2%. Secondary (hypogonadotropic) hypogonadism was the overwhelmingly dominant etiology (28.1%). Bioavailable testosterone was significantly and positively correlated with both CD4 count (ρ=0.35, p=0.005) and BMI (ρ=0.41, p=0.001). In conclusion, ART-naive men presenting with advanced HIV in this setting are caught in a syndemic of immunodeficiency, infectious disease, malnutrition, and profound endocrine dysfunction. The high prevalence of secondary hypogonadism, strongly associated with the severity of immune collapse and poor nutritional status, highlights the HPG axis as a key casualty of systemic illness. These findings provide a compelling rationale for integrating routine hormonal and metabolic screening into the initial assessment of all men newly diagnosed with HIV.